PENGARUH KARAKTERISTIK DEMOGRAFI DAN IKLIM ORGANISASI TERHADAP QUALITY OF WORK LIFE (QWL) DOSEN POLITEKNIK KESEHATAN BANJARMASIN - Tini Elyn Herlina; Ahmad Alim Bachri (Universitas Lambung Mangkurat, 2015)
This study aims to identify and analyze the influence of demographic characteristics such as: Age, Gender, Work Period, marital status, Status Employment, Income, Number of dependents and education level as well as Organizational Climate either simultaneously or partially on the Quality of Work Life lecturer Polytechnic Health Banjarmasin. The research method using a questionnaire with non-probability technique and accidental sampling obtained a sample of 69 lecturers from the Polytechnic Banjarmasin health of the population of 102 people. Measurements made with Likert scale variables and multiple linear regression analysis using software Statistical Package for the Social Science (SPSS) version 17. The research concludes that there is a significant effect simultaneously on two independent variables: demographic characteristics and organizational climate on the dependent variable: Quality of Work Life, while only partially Organizational Climate variables which indicate a significant influence on the Quality of Work Life Lecturer Polytechnic Banjarmasin